Understanding Teacher Agency of novice teachers in the context of Project-Based Learning (PjBL) - Liang, Haili; Guo, Tianwu; Zhang, Chunli (Journal of Ecohumanism, 2025)
The study explores the novice mathematics teachers’ agency in the context of Project-based Learning (PjBL) in China, which is central for ensuring the sustainability and professional development of novice teachers. Previous research has discussed the experiences of newer teachers, much less attention was paid to novice mathematics teachers’ agency. Research on how novice teachers support the varying needs of students from the inception of their careers is relatively recent. In this paper, novice teachers expressed concerns about the course requirements of PjBL, found lesson planning time consuming, and had a limited number of professional development opportunities. Nonetheless, novice teachers typically did not proactively seek assistance, and this exacerbated their feelings of pedagogical isolation. Nevertheless, the novice teachers in this study also indicated a willingness to take risks and experiment with PjBL in different ways. These different ways signaled their own beliefs about teaching, as well as accommodating the needs of diverse students, which is often what experienced teachers specialize in. Our study highlights the need for teacher education programs to ensure ongoing support and mentoring for new teachers, and to assist new teachers in articulating their needs and seeking support of other experienced teachers or experts.